CORRELATION BETWEEN RESPIRATORY FREQUENCY (RR) AND OUTCOME IN HEAD INJURY PATIENTS IN EMERGENCY ROOM OF BANGIL HOSPITAL, PASURUAN DISTRICT - Ida Zuhroidah; Ayu Dewi Nastiti; Nurul Huda; Novi Rahmania (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2018)
Background: Head injuries are a major cause of disability and death under the age of 45 years. The main focus on handling head injury patients is to prevent and limit the occurrence of secondary brain injury which will ultimately affect the outcome of the sufferer. Emergency conditions in head injury patients certainly require quick and appropriate help for better outcome outcomes.Purpose: The purpose of this study was to determine the relationship of respiratory frequency with the outcome of head injury patients in the emergency department of Bangil Hospital Pasuruan Regency.Methods: This research method is quantitative with a cross sectional approach involving 53 respondents. The sampling technique uses purposive sampling method. The outcome of head injury patients was measured using the Trauma and Injury Severity Score (TRISS) scale.Results: Data were analyzed using the Spearman test which showed a relationship p value = 0.013 <α = 0.05 so that H0 was rejected or there was a significant relationship between respiratory frequency (RR) and the outcome of head injury patients.Conclusion: The need for improvement and development of nurse resources through nursing education, emergency training and evaluation of health services at the ED. Keywords: Head Injury, Respiratory Frequency (RR), Outcome.